2018
DOI: 10.1182/blood-2018-99-117610
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Philadelphia-Negative Myeloproliferative Neoplasms in the Chilean Public Health System: Multicentric Study

Abstract: Background: Philadelphia-negative Myeloproliferative Neoplasms (Ph-MPN) are chronic hematological disorders characterized by the overproduction of one or more mature myeloid blood cell lineages. Classical Ph-MPN are Polycythemia Vera (PV), Essential Thrombocytopenia (ET) and Myelofibrosis (MF). The diagnosis includes clinical, histological and molecular features. There are not data from Chile. The aim of this study is to determinate epidemiological, clinical, diagnostic and therapeutic characteristics of Ph-MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study by Valladares et al also revealed similar results. 19 There were 46 PV patients included in this study with the median age at diagnosis of 54 years, which was slightly lower than the median age from the International Study of PV (61 years). 15 In addition, male-to-female ratio was close to 1:1, which was similar to the previous studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study by Valladares et al also revealed similar results. 19 There were 46 PV patients included in this study with the median age at diagnosis of 54 years, which was slightly lower than the median age from the International Study of PV (61 years). 15 In addition, male-to-female ratio was close to 1:1, which was similar to the previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…26 We found a lower percentage of JAK2 positive for PV and a higher percentage of JAK2 positive for PMF compared to multiple previous studies by Porto-Suares et al (93.5% of PV, 48% of ET, 60.8% of PMF), Valladares et al (86.6% of PV), and Gangat et al (66% of PMF). 19,21,22 JAK2 is involved in cellular signaling processes, such as cell proliferation, differentiation, survival, and self-renewal. Mutated JAK2 cells confer hypersensitivity to several cytokines, including erythropoietin, thrombopoietin, granulocyte colony-stimulating factor.…”
Section: Dovepressmentioning
confidence: 99%